Bimbingan Teknis Pemanfaatan Learning Management System (LMS) dalam Pembelajaran Daring untuk Guru-Guru di Kecamatan Natar - Agung Putra Wijaya; Rini Asnawati; Widyastuti; Nurain Suryadinata (FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS LAMPUNG, 2023)
Online learning is a learning interaction solution during the Covid-19 Pandemic. A Learning Management System (LMS) is essential to facilitate the implementation of online learning. Teachers can use many LMS. Schoology and Google Classroom are LMS that teachers can use in online learning. However, the facts show that most junior high school teachers need help utilizing Schoology and Google classrooms in online learning. Therefore, technical guidance activities are carried out to increase teacher knowledge, understanding, and skills in utilizing Schoology and google classroom in online learning. The method used in this activity is job training, divided into off and on-the-job training. Off-the-job training is carried out to increase teachers' knowledge and understanding of the use of Schoology and google classroom in online learning. The resulting output is an increase in teacher knowledge and experience as indicated by the n-gain between the scores before (pretest) and after (posttest) attending the training. On-the-job training is carried out to improve the skills of teachers in utilizing Schoology and google classroom in online learning. The results of this activity show an increase in teacher knowledge, understanding, and skills in using Schoology and google classroom in online learning.